Influence of Filler Metals in Welding Wires on the Phase and Chemical Composition of Weld Metal; IOP Conference Series: Materials Science and Engineering; Vol. 125 : Materials Treatment: Current Problems and Solutions - Kozyrev N. A.; Osetkovskiy I. V.; Kozyreva O. A.; Zernin E. A. Evgeny Aleksandrovich; Karthev D. S. Dmitry Sergeevich (2016, 2016)
Title screen